ANALISIS YURIDIS TERHADAP PENGUNGKAPAN PELAKU PEMBUNUHAN MELALUI TES DNA OLEH KEPOLISIAN - Andreas, Tunggul; ', Firdaus; ', Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The murder crime is a crime that is classified as a sadist, where the perpetrators of crime to kill or remove others' lives deliberately, becoming even more brutal if in fact the perpetrator of the murder was now not only kill or remove other people's lives but also cut up any part of the body of his victim. Usually these crimes depends on the psychic state of the offender, where the perpetrators are likely to suffer psychiatric disorders, but among other criminal crimes experts argue that this crime is crime following the murder of a crime with the intention to cover the crimes of murder, then then the actors perform actions following an organ mutilation (truncation) of the victim, so that the victim is known of its existence is difficult or if known, then it will mislead investigators in uncovering his identity. Keywords : : - DNA Test -Forensic -the Murder Crime